(NkITAJSKAQ (BH(NARODNAQ rESPUBLIKA (B:s (NSPRAWO^NIK (B/s - (NrAZOW(B, (NsERGEJ sERGEEWI^(B,s; (NoSTROUMOW(B, (Ng(B. (Ns(B.,s ((NmOSKWA (B:s (NiZDATELXSTWO POLITI^ESKOJ LITERATURY(B,s, 1989)
"(NkITAJSKAQ nARODNAQ rESPUBLIKA(B" - (NILL@STRIROWANNYJ POLITIKO(B-(N\KONOMI^ESKIJ SPRAWO^NIK(B. (NsODERVIT BOLX[OJ FAKTI^ESKIJ I CIFROWOJ MATERIAL O RAZLI^NYH OBLASTQH SOCIALISTI^ESKOGO STROITELXSTWA W knr(B, (NDOSTIVENIQH TRUDQ]IHSQ STRANY(B.s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NeKONOM)QÆKAs)E -- (NkITAJSXKA nARODNA rESPUBL)QÆKAs)E; (NkITAJs